2017
DOI: 10.1080/09513590.2017.1393064
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related osteoporotic vertebral compression fractures in two patients treated with low-molecular-weight heparin during pregnancy: case reports

Abstract: Pregnancy-related osteoporosis (PRO) is an uncommon metabolic bone disease that can result in vertebral fragility fractures. Here we report two cases of young women who had been previously treated with LMWH-enoxaparin and were diagnosed with PRO with vertebral fragility fractures after delivery. In first case report, a 33-year-old primigravid woman who was treated with 40 mg/day of enoxaparin for eight months to prevent venous thromboembolism was presented. After delivery, Dual energy X ray absorptiometry (DEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…3,4 There are reports of PAO in women treated with enoxaparin. 5,6 In contrast, an observational cohort study of 152 women who had received LMWH during pregnancy concluded that LMWH use was not associated with a subsequent decrease in BMD and osteoporotic fractures. 7 In the largest case series of PAO, which compared 102 PAO patients with 102 healthy controls, LMWHs were not introduced as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 There are reports of PAO in women treated with enoxaparin. 5,6 In contrast, an observational cohort study of 152 women who had received LMWH during pregnancy concluded that LMWH use was not associated with a subsequent decrease in BMD and osteoporotic fractures. 7 In the largest case series of PAO, which compared 102 PAO patients with 102 healthy controls, LMWHs were not introduced as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Although heparin has mainly been implicated as a risk factor for PAO, several animal studies have shown that low molecular heparins (LMWHs) like enoxaparin dose dependently inhibit osteoblasts proliferation and impairs the mechanical properties of bone 3,4 . There are reports of PAO in women treated with enoxaparin 5,6 . In contrast, an observational cohort study of 152 women who had received LMWH during pregnancy concluded that LMWH use was not associated with a subsequent decrease in BMD and osteoporotic fractures 7 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of informarion about acute postpartum osteoporosis mainly when the patient have not Received any kind of heparin. Recently, Osturk et al [1] have informed about two cases of osteoporotic disease during pregnancy but associated to the heparin administration. He reported two cases of vertebral fractures diagnosed by Nuclear Magnetic Resonance (RMN).…”
Section: Introductionmentioning
confidence: 99%